INFLUENCE OF THE METEOROLOGICAL CONDITIONS ON FOREST FIRES OCCURRENCES IN LICHINGA DISTRICT, NORTHERN MOZAMBIQUE - Mbanze, Aires Afonso; Batista, Antonio Carlos; Tetto, Alexandre França; Koehler, Henrique Soares; Manteiga, Jose Bernardo (Floresta, 2015)
Abstract The aim of this study was to assess the influence of meteorological conditions on the fire occurrences in forest stands of Lichinga district, in the period from 2010 to 2012. Data about fire occurrences records of the district of Lichinga and two others close districts (Lago and Sanga) were provided by the Center for Monitoring and Control of Forest Fires (CCMIF) of the company Chikweti. Daily weather data: temperature, rainfall and relative humidity of the same period, recorded at 13:00 PM, by the meteorological station of the Institute of Agronomic Research of Mozambique (IIAM) in Lichinga district were also provided to this work. Meteorological data were submitted to regression analysis and Tukey test. The results showed a significant variation in temperature and humidity on both tests. The overlapping of fire occurrences and meteorological variables, suggested a great influence of the meteorological conditions in the occurrence of fires, mainly due to the very long dry periods. In 2010 there was a delay in the occurrence of fires; this was related to the rainy season which was slightly longer. September and October was the months that recorded the highest number of fire occurrences throughout the studied period. Resumo Influência das condições meteorológicas na ocorrência dos incêndios florestais no distrito de Lichinga, norte de Moçambique. O objetivo deste estudo foi avaliar a influência das variáveis meteorológicas na ocorrência de incêndios em povoamentos florestais no distrito de Lichinga, no período de 2010 a 2012. Para tal, foram analisados os registros de ocorrências de incêndios do distrito de Lichinga e de outros dois distritos vizinhos (Lago e Sanga), disponibilizados pelo Centro de Controle e Monitoramento de Incêndios Florestais (CCMIF) da empresa Chikweti Forest of Niassa, e dados meteorológicos diários de temperatura (máxima e mínima), precipitação e umidade relativa, do mesmo período, registrados às 13 horas, pela estação meteorológica do Instituto de Investigação Agronômica de Moçambique em Lichinga (IIAM-Lichinga). Os dados meteorológicos foram submetidos ao teste de análise de regressão e ao teste de Tukey, tendo sido observado uma variação significativa da temperatura e umidade em ambos os testes. A sobreposição das ocorrências dos incêndios com as variáveis meteorológicas demostrou uma grande influênca dessas variáveis na ocorrência dos incêndios, principalmente devido aos períodos secos prolongados. No ano 2010 observou-se um atraso na ocorrência dos incêndios, devido ao período chuvoso que foi ligeiramente mais longo. Os meses que registraram maior número de ocorrências em todo o período foram setembro e outubro. Palavras-chave: Povoamentos florestais; variáveis meteorológicas; prevenção de incêndios florestais.